Strategi Komunikasi Pengelola West Bandits Dalam Membangun Brand Awareness Menggunakan Media Sosial Instagram - Stephanie Olivia Erika; Satya Candrasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
West Bandits Combiphar Solo is a basketball club that has been trying to introduce its brand using Instagram since its debut. By using Instagram, they try to make their brand known to basketball lovers. This will be a focus that will be examined by researchers to examine more deeply the use of West Bandits Instagram Media as a Means in Building Brand Awareness. The method in this research is a case study, this type of research is descriptive and conducts interviews, reads written sources in the form of books, and documentation in the form of photographs. The results of this study are that West Bandits have succeeded in raising their level of awareness from not being aware of the brand to having brand awareness. They also upload activities and accompany public opinion by hiring public figures to increase their brand awareness. The suggestion in this research is that West Bandits continue to improve content in using their Instagram social media.